Changes in Activity of the Same Thalamic Neurons to Repeated Nociception in Behaving Mice. - Yeowool Huh; Jeiwon Cho (PLoS ONE, 2015)
The sensory thalamus has been reported to play a key role in central pain sensory modulation and processing, but its response to repeated nociception at thalamic level is not well known. Current study investigated thalamic response to repeated nociception by recording and comparing the activity of the same thalamic neuron during the 1st and 2nd formalin injection induced nociception, with a week interval between injections, in awake and behaving mice. Behaviorally, the 2nd injection induced greater nociceptive responses than the 1st. Thalamic activity mirrored these behavioral changes with greater firing rate during the 2nd injection. Analysis of tonic and burst firing, characteristic firing pattern of thalamic neurons, revealed that tonic firing activity was potentiated while burst firing activity was not significantly changed by the 2nd injection relative to the 1st. Likewise, burst firing property changes, which has been consistently associated with different phases of nociception, were not induced by the 2nd injection. Overall, data suggest that repeated nociception potentiated responsiveness of thalamic neurons and confirmed that tonic firing transmits nociceptive signals.